2020
DOI: 10.3390/plants9060734
|View full text |Cite
|
Sign up to set email alerts
|

Light Interception and the Growth of Pastures under Ideal and Stressful Growing Conditions on the Allegheny Plateau

Abstract: Pasture-based livestock production is impacted by management and weather. In pastures, there is conflict between leaf retention for plant growth and leaf harvest for animal nutrition. Defoliated pastures with low light interception (LI) may have a low forage growth rate (FGR), while excessive growth shades leaves, reducing FGR and resulting in an S-shaped regrowth curve. To optimize production, it is best to keep FGR linear. Three studies were conducted to evaluate the impact of management and weather on FGR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Light interception is one of the primary drivers of plant growth together with nutrients, temperature and available soil moisture (Rayburn and Griggs, 2020). Previous studies that were conducted in artificial shade conditions (Varella et al, 2001;Dodd et al, 2005) or in silvopastoral systems (Devkota et al, 2009) reported that light was the main determining factor for the understory forage production.…”
Section: Shade and Animal Trampling Reduced The Pasture Production In Fully Shaded Areas In Solar Pasturesmentioning
confidence: 99%
“…Light interception is one of the primary drivers of plant growth together with nutrients, temperature and available soil moisture (Rayburn and Griggs, 2020). Previous studies that were conducted in artificial shade conditions (Varella et al, 2001;Dodd et al, 2005) or in silvopastoral systems (Devkota et al, 2009) reported that light was the main determining factor for the understory forage production.…”
Section: Shade and Animal Trampling Reduced The Pasture Production In Fully Shaded Areas In Solar Pasturesmentioning
confidence: 99%
“…Regarding the effect of tree canopy on pasture productivity, the competition for resources water, light, and nutrients are considered as the main reason for decreased yields UTC in winter and especially in spring [15,16]. However, given that tree canopy contributes to less pasture evapotranspiration and, as a consequence, guarantees higher soil moisture content [19], and also because UTC areas are usually more fertile [19], the critical factor for the lower pasture productivity under tree canopy must result from the combination of four sub-factors: (i) lower incidence of solar radiation, which affects directly the physiological processes of plants and net DM production [15], since light interception by plant leaves is used in photosynthesis to provide energy for plant maintenance, to grow new leaves and roots, and to produce carbohydrates [36]; (ii) lower land cover, due to the release of inhibitory substances resulting from leaves and other tree residues [32]; (iii) development of less productive botanical species; Graß et al [16] highlight the shadow inhibitor effects specifically on the growth of legumes; and (iv) livestock grazing, which, according to Hussain et al [37] can have an important influence on sward composition, quality and production UTC and OTC.…”
Section: Variability Pattern Of Pasture Productivity and Qualitymentioning
confidence: 99%
“…Tree canopy effect is potentially positive for the development of the pasture in winter, preventing the soil/pasture surface temperature from falling to values close to 0 • C. On the other hand, the lower soil/pasture surface temperature UTC during spring months may have a positive effect on the pasture by delaying the conclusion of the vegetative cycle (and the consequent quality degradation) [42], but it may also lead to lower pasture productivity in these areas, reflecting lower light transmission to the understory and, consequently, the reduction of photosynthetic rates in zones with lower sun exposure [43]. Light interception by plant leaves is used in photosynthesis to provide energy for plant maintenance, to grow new leaves and roots, and to produce carbohydrates stored within cells and translocated to energy sinks [44].…”
Section: Discussionmentioning
confidence: 99%